Exposure to violence and academic achievement in Iraq - Al-Hemiary, Nesif J. (Journal of the Faculty of Medicine Baghdad, 2015)
Background: Iraqis were exposed to wars, widespread violence and civil war. Post-traumatic stress disorder develops after exposure to trauma and violence. It has a negative effect on academic achievement of the students. Objective: This report was carried out to study the effect of exposure to violence on academic achievement of youths in Iraq. Methods: A total of 319 university students from Baghdad were included in the study. Their age ranged between 18 and 24 years with male to female ratio of 0.6:1. A questionnaire was filled for each participant. Requested data were demographic information, data on school achievement and Harvard Trauma questionnaire (exposure to war trauma, posttraumatic stress disorder “PTSD”). Chi square was used to examine the association between PTSD and poor academic achievement. Student’s t test was used to demonstrate the difference in exposure between students with poor and good academic achievement. P value < 0.5 was considered as significant. Results: Post- traumatic stress disorder was observed in 21.9% of students. Poor academic achievement was noticed in 32.9% of students with post-traumatic stress disorder. Academic achievement was not significantly associated with post-traumatic stress disorder (p=0.8). Significant difference was found in score of exposure to violence between students with poor and good academic achievement (p= 0.001). Conclusion: Exposure to violence had a negative effect on academic achievement